Learning from other Domains to Advance AI Evaluation and Testing: The Evolving Use of Bank Stress Tests - Judge, Kathryn (2025)
“Stress testing” of banks, or more accurately, banking organizations, is one of the most important regulatory innovations to emerge from the 2008 financial crisis. The stress testing of an individual bank entails assessing how that bank will fare under a given adverse scenario, usually meant to replicate the types of developments that would occur during a deep or prolonged recession, such as a significant rise in unemployment, heightened market volatility and large declines in asset values. Typically, the regulator will provide one or more scenarios, the bank then provides the requisite data and the regulator uses its model to assess how the bank will fare in the face of the scenarios provided. If the regulator determines that the bank would not remain in good enough health, in the sense of remaining well capitalized in the face of the hypothetical adverse scenario, it usually requires the bank to increase its capital by foregoing distributions to shareholders via dividends or share repurchases. A bank’s capital refers to the amount of equity it uses to fund its operations; higher capital increases a bank’s capacity to absorb losses. Banks also engage in bank-run stress tests using their internal risk-management tools as part of their obligations, providing separate insights into the quality of a bank’s risk management regime. The benefits of regulatory stress testing are many, as are the challenges. They vary depending on the conditions under which the stress tests are run. The original regulatory stress tests occurred in early 2009, when the financial system remained mired in the Great Financial Crisis (GFC). This allowed bank regulators to devise an adverse scenario based on the actual and specific hardships the economy was already facing. Bank regulators were willing to subject banks to a rigorous and realistic stress test because Congress had already given the Treasury Department 700 billion in funding that the Treasury Department could use to recapitalize any bank revealed to have deficiencies that it could not remediate by raising additional funds from market-based sources. This was critical to the rigor and credibility of the exercise, as bank regulators are hesitant to undertake any public exercise that might reveal adverse information or otherwise exacerbate financial fragility unless they have the tools to contain the fallout. With the benefit of the temporarily more expansive authority and other wise design choices, the original round of stress tests helped provide credible information about bank health and enhanced the functioning of the financial sector, helping to further pave the road to recovery.